MARKETING MODELS APPLICATION EXPERIENCE - A. Yu. Rymanov; T. V. Titova; Z. K. Likhanova (Модернизация, инновация, развитие, 2016)
Marketing models are used for the assessment of such marketing elements as sales volume, market share, market attractiveness, advertizing costs, product pushing and selling, profit, profitableness. Classification of buying process decision taking models is presented. SWOT- and GAPbased models are best for selling assessments. Lately, there is a tendency to transfer from the assessment on the ba-sis of financial indices to that on the basis of those non-financial. From the marketing viewpoint, most important are long-term company activities and consumer drawingmodels as well as market attractiveness operative models.